The Public's Right to Health: When Patient Rights Threaten the Commons - Elizabeth Weeks Leonard (Washington University Law Review, 2009)
This Article offers a contemporary examination of traditional public health objectives to address social problems not amenable to individual resolution. Taking the tradition a step further, it defines a “public health right” that may justify certain government actions that otherwise appear to impair individual rights. For example, lawmakers are considering whether current regulations on prescription drugs should be loosened to allow terminally ill patients to access drugs before they have been tested and approved for the general public. This Article concludes that expanding access to experimental drugs would violate the public health right to scientific knowledge and new drug development. The choice of a few patients to avail themselves of untested drugs depletes the “commons” of biomedical research. The Article concludes by briefly testing the public health right against other contemporary laws intended to promote public health and welfare, finding some but not all are justified.
Keywords: Patients -- Civil rights; Medicine; Experimental; Drugs -- Research; Commons; Cost effectiveness; Health care industry